Around Holiness – Considerations from the Cultural Point of View - Grad, Jan (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The development of the concept of holiness is associated with the cultural process of separating the practical activity and the primary magical beliefs, termed by Max Weber's the ‘disenchantment of the world’. As a result, the sphere of human activity was divided into the sacred and the profane. Holiness was generally associated with the operation of variously recognised supernatural factors. In the Judeo-Christian tradition, it is an attribute of God's holiness. As a generalisation of all the virtues, it is endowed with the ethical dimension. The moral dimension of holiness and the specific rules of behaviour towards the sacred are reflected in everyday language,several sayings and proverbs.